2011
DOI: 10.1002/cbic.201100241
|View full text |Cite
|
Sign up to set email alerts
|

N‐Sulfanylethylanilide Peptide as a Crypto‐Thioester Peptide

Abstract: Native chemical ligation (NCL) has shown great utility in protein chemistry and has yielded impressive success in the preparation of a wide variety of proteins.[1] This methodology requires peptide thioesters that serve as chemoselective acylating agents for N-terminal cysteinyl peptides to afford ligated peptides through a sequence of reactions consisting of S-S and S-N acyl transfers. The susceptibility of the thioester moiety to basic reagents has necessitated the preparation of the key intermediate by Boc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 65 publications
1
76
0
Order By: Relevance
“…23 Previous synthetic strategies involved several experimental manipulations including purification after the first NCL, removal of the N-terminal cysteine protection (C-to-N) and conversion of thioacid to thioester (N-to-C), which resulted in low overall yields. Recently, we discovered that the N-sulfanylethylanilide (SEAlide) peptide efficiently functions as a thioester equivalent in the presence of phosphate salts to participate in NCL [24][25][26] (Scheme 1a). This feature enables the SEAlide peptide to enhance the performance of an N-to-C-directive one-pot/sequential NCL protocol (Scheme 1b).…”
Section: Chemistrymentioning
confidence: 99%
“…23 Previous synthetic strategies involved several experimental manipulations including purification after the first NCL, removal of the N-terminal cysteine protection (C-to-N) and conversion of thioacid to thioester (N-to-C), which resulted in low overall yields. Recently, we discovered that the N-sulfanylethylanilide (SEAlide) peptide efficiently functions as a thioester equivalent in the presence of phosphate salts to participate in NCL [24][25][26] (Scheme 1a). This feature enables the SEAlide peptide to enhance the performance of an N-to-C-directive one-pot/sequential NCL protocol (Scheme 1b).…”
Section: Chemistrymentioning
confidence: 99%
“…This reaction involves two sequential rearrangements since the process starts with an N,S-acyl shift of the SEA tertiary amide group, and finishes with an S,N-acyl shift at the level of the transient thioesterlinked intermediate formed by a classical NCL reaction mechanism. Other studies showed that the capacity of SEA peptides to be transamidated by N-terminal cysteinyl peptides in water at a pH close to neutrality is shared by other N,S-acyl shift systems such as the SEAlide [28], the N-alkylcysteine [15,29 ] or the a-methyl cysteine The design of selective peptide transamidation (a) or amide metathesis (b) reactions is highly challenging. Up to now, peptide-based dynamic covalent libraries relied on non-peptidic reversible reactions such as the thiol/disulfide (c), the amine/imine (d) or the thiol/thioester exchange reactions (e).…”
Section: Dynamic Selection Of the Combination With Stronger Affinitymentioning
confidence: 99%
“…10,11 Another study relied on the differential reactivity of thiolester surrogates for setting up a kinetically controlled ligation scheme. 9 Fundamentally, the process described in Figure 4 differs from the previous studies in several aspects. First, only one carbonyl functionality can react at a time, i.e., the process is not kinetically controlled.…”
Section: Organic Lettersmentioning
confidence: 87%